Pancreatic metastasis in a case of small cell lung carcinoma diagnosed by EUS - Tarkan Karakan; Mustafa Cengiz; Mehmet İbiş and Nalan Akyürek and Selahattin Ünal (Turkish Journal of Gastroenterology, 2019)
Small-cell lung carcinoma represents a group of highly malignant tumors characterized by early and widespread metastais even at the time of diagnosis. However, the pancreas is a relatively infrequent site of metastasis by this neoplasm. A 57-year-old patient was admitted with an intense cough and complaints of abdominal discomfort. A chest X-Ray showed no evidence of lung mass but did show signs of lymphadenopathy. In addition, there was little evidence for malignancy based on a transbronchial needle aspiration. In contrast, there was a mass in the head portion of the pancreas. We diagnosed a case of small-cell lung carcinoma metastasis in the pancreas by using an endoscopic ultrasound-guided fine-needle aspiration biopsy. This case demonstrates that endoscopic ultrasound-guided fine-needle aspiration biopsy is an important tool in the diagnosis of metastatic pancreatic neoplasms.